The pedagogisation of health knowledge and outsourcing of curriculum development: the case of the Stephanie Alexander Kitchen Garden initiative. Issue 2 (3rd March 2020) - Rossi, Tony; Kirk, David
ABSTRACT: It is apparent that the dimensions of health within and under the auspices of schooling are open to contributions by other providers that exist outside of school systems. We acknowledge schools often resort to outside providers for a number of reasons; for example, to broaden the curriculum experiences for children, or to compensate for the absence of expertise within a school. The central focus for this paper is to try to understand these phenomena with particular reference to the Stephanie Alexander Kitchen Garden initiative. through the theoretical work of Basil Bernstein. Specifically, we were interested in the source of particular kinds of health knowledge for the purposes of acquisition by children, what journey does such knowledge travel to arrive in school classrooms and in the process, how and in what ways is it pedagogised under the conditions of outsourcing?